Edible films based on nanostructured starch as barrier material moisture - Vázquez-Luna, Alma (Universidad Autónoma de Tamaulipas, 2019)
The packaging materials provide physical protection and create the appropriate physicochemical conditions to give an adequate shelf life. Recently, the food industry has proposed to incorporate nanocomposites into edible films that degrade in a short period of time without causing environmental problems. The objective of this research was to develop an edible film using nanostructured starch, which can serve as a packaging, resistant to moisture, stable that can extend the shelf life of food and additionally environmental benefits. The effects of nanostructured starch on the physical and structural properties of an edible film were studied in terms of thickness, water solubility, diffusion, water vapor permeability (WVP) and water vapor transmission rate (WVTR). The results showed that the edible films formulated with nanostructured starch had the lowest thickness. Furthermore, the solubility in water, the diffusion coefficient, WVP and WVTR were lower for these films. The nanostructuring of corn starch made it possible to obtain edible films with excellent water barrier properties without modifying the structural properties of the polymer matrix, which could constitute an alternative for food packaging.